Climate projections of the Adriatic Sea: role of river release - Verri, Giorgia; Furnari, Luca; Gunduz, Murat; Senatore, Alfonso; Santos da Costa, Vladimir; De Lorenzis, Alessandro; Fedele, Giusy; Manco, Ilenia; Mentaschi, Lorenzo; Clementi, Emanuela; Coppini, Giovanni; Mercogliano, Paola; et al. (Frontiers in Climate, 2024)
The Adriatic Sea, characterized by unique local features in comparison to the broader Mediterranean Sea, stands out as a highly susceptible region to climate change. In this context, our study involves a focused climate downscaling approach, concentrating on the Adriatic's water cycle. This encompasses integrated modeling at the mesoscale, covering the atmosphere, hydrology, and marine general circulation. The study period spans from 1992 to 2050, considering the high emission scenario RCP8.5.We aim at evaluating how the river release projection affects the local density stratification and the sea level rise. Indeed, the river release is found to decrease by about 35% in the mid-term future and to condition the stratification of the water column with differences between the Northern and Southern sub-basins.The projected runoff decrease has a major impact on the Northern sub-basin, where the stratification is haline-dominated and the foreseen salinization prevails on the heating through the whole water column. Conversely, the runoff decrease has a lower impact in the Southern sub-basin, where the future changes of other mechanisms may play a major role, e.g. the changing properties of the Mediterranean water entering the Otranto Strait, and the foreseen heating prevails on the salinization at the intermediate to deep water column.The study provides a first evidence of how the decreasing river discharge locally reduces the density stratification, increases the dense water and mitigates the sea level rise in the Northern Adriatic Sea, thus acting in the opposite direction to the global warming.In order to minimize uncertainty in coastal ocean projections around the word, it is essential that the climate downscaling integrates high-resolution hydrology and hydrodynamics models to correctly reproduce the link between surface buoyancy and stratification and thus the resulting dynamics.